Q: How do you factor out 3x2 plus 54x plus 243?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6x + 54x -9 = 60x - 9

(3x - 1)(3x + 19)

18t + 4x -47t + 50x = -29t + 54x

The "answer" is a pair of numbers that, if you put one of them in place of 'x' and the other one in place of 'y', then the statement "-3y = -54x + 18" is true. There are an infinite number of different correct "answers".

It's not something that can have a SOLUTION unless it EQUALS something. x + 53x = 54x. Does 54x = 1? Then x = 1/54. Does 54x = 108? Then x = 2. etc.

Related questions

6x + 54x -9 = 60x - 9

(3x - 1)(3x + 19)

Yes, I do. 152x + 11

18t + 4x -47t + 50x = -29t + 54x

The "answer" is a pair of numbers that, if you put one of them in place of 'x' and the other one in place of 'y', then the statement "-3y = -54x + 18" is true. There are an infinite number of different correct "answers".

It's not something that can have a SOLUTION unless it EQUALS something. x + 53x = 54x. Does 54x = 1? Then x = 1/54. Does 54x = 108? Then x = 2. etc.

2x - 10 = 44 + 8x2x = 54 + 8x-6x = 54x = -9

Dividing all terms by 6 gives: 9x2+24x+16 = (3x+4)(3x+4) when factored

The GCF is 6x

the square root of fluffiness

3x5+ 15x3+ 12xAll of these terms have a common factor of 3x, so we can factor it out to get:3x(x4+ 5x2+ 4)Our 'bracketed' term now has the layout of a quadratic equation, except the powers of x have been doubled - x2+ 5x + 4x0(x0= 1, x0*2= x0)This means we can factorise it just like a quadratic, except making sure the x's are squared in the final brackets.x2+ 5x + 4 factorises to (x+1)(x+4), so x4+ 5x2+ 4 will factorise to give (x2+1)(x2+4).Put this all together to get:3x(x2+1)(x2+4)This could be factorised further by treating each of these new bracketed terms as quadratics, but only if complex numbers are allowed - so for simplicity's sake, this is the final product.Otherwise, you could turn it into:3x(x+i)(x-i)(x+2i)(x-2i)

x + 15 = 54x = 54 - 15 = 39ANSWER: 39